SOSIALISASI KKN TEMATIK MBKM PENDAMPINGAN PEMBUATAN STRUKTUR PERHITUNGAN HARGA POKOK PRODUKSI GUNA PENENTUAN HARGA JUAL KERIPIK SINGKONG RASA JAGUNG DI DESA PETANANG - Pratiwi, Anggun Nia; Lestari, Della Ayu; Rahmayang, Tito; Hertati, Lesi; Hendarmin, Rum; Syafitri, Lili; Munandar, Aris (Transpublika Publisher, 2022)
MSME is a form of business that can provide many benefits and benefits for the community. The existence of these micro-enterprises is increasing rapidly and mushrooming in every corner of the region throughout Indonesia. There are various obstacles faced by MSME actors in running their business. One of the problems faced is that business actors are still having difficulty determining the Cost of Production (HPP) and the selling price of the product. Calculating the selling price of a product clearly and definitely is important for business actors. The right calculation will provide benefits in accordance with the expectations of the business actor. Based on the results of our initial survey in Petanang Village, namely the lack of assistance in determining the Cost of Production (HPP) and Product Selling Prices. The PKM Team employs socialization to help provide insight in estimating the Cost of Production and determining the Selling Price of Cassava Chips as a means of resolving the problem.